Management of global animal genetic resources organizational and institutional structure - Fitzhugh, H.A.; Strauss, M.S. (Food and Agriculture Organization of the United Nations, 1992)
The paper is divided in five parts. 1. Approach to conservation, 2. conservation activities, 3. plant conservation experience and 4. organizational and institutional structure for livestock programmes. The first part discusses the maintainance of breeding populations and cryopreservation of gametes and embryos. The second part examines inventory and characterization of existing populations, genetic evaluation, maintenance, research, training and public awareness. The third part looks into the national and international programmes as well as the private industry. The fourth part summarises the important elements of national programmes, viz, inventory, characterization and documentation, conservation of unique and threatened populations, collaboration with other conservation programmes, research and policy. The international programmes are also discussed with particular reference to institutes within CGIAR and FAO.